2022
DOI: 10.1088/1742-6596/2305/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of valuable heavy minerals via gravity and magnetic separation operations from Diit Quaternary stream sediments, southern coast of the Red Sea, Egypt

Abstract: This research aims to concentrate and recover valuable heavy minerals (VHMs) contained in Diit area, southern coast of the Red Sea, Egypt. In this study, three technological samples were collected representing Lens, Delta and Wadi Diit; mineralogical investigation followed by mineral processing was performed in order to recover VHM content. VHMs such as zircon, ilmenite, rutile, sphene, apatite, garnet, and magnetite have been recorded in associations with lesser amounts of uranothorite, monazite, xenotime, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Prior to repurposing Pb-Zn slag in the construction sector, it is important to analyze its mineralogical composition for the extraction of critical metals with economic potential, such as Pb, Zn, and Ag. As a result, procedures, such as gravity concentration and separation techniques, are being used to convert metal concentrations into a collective concentrate from which the maximum amount of one or more elements can be extracted [15,16]. Once valuable metal elements are extracted from the slag, the residual raw material has to be reapplied in order to close the cradle-to-cradle circle and achieve the zero-waste goal.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to repurposing Pb-Zn slag in the construction sector, it is important to analyze its mineralogical composition for the extraction of critical metals with economic potential, such as Pb, Zn, and Ag. As a result, procedures, such as gravity concentration and separation techniques, are being used to convert metal concentrations into a collective concentrate from which the maximum amount of one or more elements can be extracted [15,16]. Once valuable metal elements are extracted from the slag, the residual raw material has to be reapplied in order to close the cradle-to-cradle circle and achieve the zero-waste goal.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the recoveries of monazite were 94.8% and 76.6%, respectively, when magnetic separation and gravity separation were separately carried out. M M Fawzy et al [22] recovered valuable heavy minerals from the southern coast of the Red Sea by shaking table, followed by magnetic separation. The results presented that the recoveries of heavy minerals reached 91.68%, 71.67% and 82.06%, respectively from three different areas.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the extraction of valuable metals such as Pb, Zn, and Ag has economic potential. Therefore, methods such as gravity concentration and magnetic separation are employed to create metal concentrates into their collective concentrate, from which the maximum amount of one or several elements can be extracted [15,16]. Production of construction material could be a viable way to sustainably utilize Pb and Zn slags with a financial return, given their quantity and mineralogical composition, especially if the final products could be manufactured and sold locally [17].…”
Section: Introductionmentioning
confidence: 99%